Economics of Raising Seedling of Broccoli (Brassica oleracea L. var. Italica) in Protected Structure - Sojitra, M. A.; Satasiya, R. M.; Chauhan, P. M.; Parmar, H. V.; Patel, D. V.; Prajapati, G. V. (International Journal of Economic Plants, 2022)
The experiment was conducted during 2020−21 and 2021−22 at Green house complex, AICRP on Plastic Engineering in Agriculture Structure and Environment Management, Departmental of Renewable Energy Engineering, College of Agricultural Engineering and Technology, Junagadh, Gujarat, India to study the economics of vegetable seedling nursery for high valued broccoli crop for profitable entrepreneurship. Timely sowing and optimizing plant population significantly increase vegetable production. The availability and required seedling in time play a major role in vegetable cultivation. The seedlings of broccoli are transplanted in the rabi season, therefore, farmers have to prepare seedlings in the late monsoon. The germination percentage and survival of seedlings are reduced due to extreme weather condition like frosting, freezing, heat wave, high temperature and excess soil moisture in the open field. Therefore, present work was carried out on the economic feasibility of seedling raising of broccoli in a natural ventilated net-cum-poly house. The seeds of broccoli of Namdhari seeds of F1 were sown in a plug tray in the month of September of the year 2020 and 2021. Plug trays were filled with the mixture of cocopeat and vermicompost in an equal proportion of 1:1 (V/V). The germination was recorded at 94% and each seedling of broccoli was sold for ` 1.60. The Gross Return (GR), Net Return (NR), and benefit-cost ratio of the seedling raising of broccoli were recorded as Rs. 556.80 m-2, Rs. 262.69 m-2 and 1.89, respectively.